LEGAL ASPECTS OF THE CENTRAL BANK’S GREEN FINANCE INSTRUMENTS IN INDONESIA: AN OVERVIEW - Ratu Silfa Addiba Nursahla; Nismara Paramayoga; Muhammad Anas Fadli; Muhammad Pravest Hamidi (Journal of Central Banking Law and Institutions, 2023)
For experts in the field of central banking, the growth of green finance presents a significant opportunity for of research. This rapid emergence of green finance springs from the urgent need to address the threat of climate damage and the important role of central banks in supporting this transition to sustainability. In this study, we utilise the legal instruments framework proposed by Volz to analyse the legal aspects of green finance within the context of the central bank in Indonesia. Our findings indicate that Bank Indonesia, as well as the Financial Service Authority, has a range of regulatory tools at its disposal to influence borrowing and lending policies, as well as investment choices. Several green finance instruments have been created under Indonesian laws and regulations, including loan to value/finance to value, green finance guidelines and frameworks, and affirmative measures to support green finance. The future of the legal framework on green finance in Indonesia looks promising, with the implementation of sustainable finance from businesses and support from the government. However, there is still room for Bank Indonesia to adopt additional regulatory instruments, such as incentives for redirecting resources to low-carbon investments to further promote sustainable finance.